E ASSESSMENT OF ORO-DENTAL HEALTH STATUS USING THE CAO AND EGOHID INDEXES AT THE YOUNG PEOPLE - Ioan Dănilă; Iulia Săveanu; Carina Balcoș (Romanian Dental Association for Education, 2015)
CAO and CAOS epidemiological indices provide significant information for an overview assessment of dental health but can not make a nuanced type of carious lesions and involvement of the need for treatment. EGOHID system of clinical assessment and restoration of carious lesions provide evidence on lesion topography guided us on the degree of dental damage in motivating action supporting our dental health. The purpose of this study was to evaluate the comparative in terms of dental health indices CAO, CAOS and EGOHID system. Materials and methods: The study was conducted on a sample of 122 subjects with a mean age 23.53 years in which data were collected on the type of carious lesion and the type of restoration. Data were collected by clinical examination and observation files recorded according to codes. All patients in the study were informed verbally about the purpose of the study noting their consent. Statistical data processing was performed with SPSS 14.00 for Windows fixing the threshold of statistical significance of p ≤ 0.05. Results and discussion: Comparative analysis of two systems of assessment revealed that significant differences p ≤ 0.05 for the system of assessment of dental status in the system component EGOHID carious lesions, lesion assessment is accomplished underestimated component CS of CAOS index showing an average of 4.42 (± 4.132) compared with EGOHIDC is the index of the cavity showing an average of 10.38 (± 7.484). Conclusion: Data obtained through evaluation of dental caries is higher, providing a concrete image of the orientation dentistry, early diagnosis of dental caries, treatment and hence the technicallity and restorative treatments.